2015
DOI: 10.1016/j.fct.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the xenobiotic transformation system and inflammatory response by ochratoxin A exposure using a co-culture system of Caco-2 and HepG2 cells

Abstract: Cytotoxicity of ochratoxin A (OTA) was evaluated using the MTS assay, and membrane integrity was measured using transepithelial electrical resistance (TEER). A transwell system was used to investigate the effect of OTA on the expression of the CYP450 (1A1, 2A6, 2B6, 3A4 and 3A5), NAT2, COX-2, LOX-5, and MRP2 genes in Caco-2 and HepG2 cells. TEER decreased by a mean of 63.2% after 24 h in Caco-2 differentiated cells without inducing cell detachment; revealing damage to the intestinal epithelial cell tight junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…Several genes have been identified in the CYP3A subfamily of mammals (for example, five in rat and four in human), but the expression of these genes in renal tissues has been poorly investigated [96]. In terms of gene expression, Ayed-Boussema et al (2012) [63] and Gonzalez-Arias et al [97] described an increase of expression levels in all cytochromes assayed (CYP3A4, 2B6, 3A5, and 2C9) in a primary human hepatocyte culture. Previous studies have reported various results regarding the effects of AFB1 and OTA in primary cultured human hepatocytes in which increasing concentrations of these mycotoxins clearly induced CYP3A4 and CYP2B6 mRNA levels in a dose-dependent manner [63].…”
Section: Discussionmentioning
confidence: 99%
“…Several genes have been identified in the CYP3A subfamily of mammals (for example, five in rat and four in human), but the expression of these genes in renal tissues has been poorly investigated [96]. In terms of gene expression, Ayed-Boussema et al (2012) [63] and Gonzalez-Arias et al [97] described an increase of expression levels in all cytochromes assayed (CYP3A4, 2B6, 3A5, and 2C9) in a primary human hepatocyte culture. Previous studies have reported various results regarding the effects of AFB1 and OTA in primary cultured human hepatocytes in which increasing concentrations of these mycotoxins clearly induced CYP3A4 and CYP2B6 mRNA levels in a dose-dependent manner [63].…”
Section: Discussionmentioning
confidence: 99%
“…These TJ protein localization effects were confirmed by transmission electron micrographs [ 57 ]. OTA treatment resulted in intestinal barrier dysfunction, which was confirmed by increased cell permeability and microvilli disruption and TJ proteins in various cell culture systems [ 82 , 105 ]. These observations could be explained by ROS/Ca 2+ -mediated myosin light chain kinase (MLCK) activation [ 128 ].…”
Section: Intestinal Dysfunction Induced By Mycotoxinsmentioning
confidence: 99%
“…OTA down-regulated the gene expression of cyclooxygenase-2 (COX-2) and lipoxygenase-5 (5-LOX) genes in Caco-2 cells, which have been regarded as inflammatory mediators [ 105 ]. The mRNA expressions of pro-inflammatory cytokines including interleukin-1 beta (IL-1β), IL-6, IL-8, COX-2, and tumor necrosis factor-alpha (TNF-α) were increased in the DON-exposed porcine intestinal epithelial cells, with DON-mediated inflammation partially dependent on ROS production and MAPK pathway activation [ 106 , 151 , 152 , 153 , 154 ].…”
Section: Intestinal Dysfunction Induced By Mycotoxinsmentioning
confidence: 99%
“…The in vitro co-culture system may offer suitable alternative to in vivo animal testing and it represents an indispensable tool to approximate the complex conditions in studies aimed at mycotoxin action mechanism in an organism [43]. There have been a few co-culture models used in vitro for studying the absorption of natural bioactive compounds and drug toxicity in hepatocytes [35,[43][44][45]. However, this co-culture system was not used to test the efficacy of silibinin in preventing the effects of mycotoxins.…”
Section: Mycotoxins Effectsmentioning
confidence: 99%